Cross-listing and operating performance: evidence from exchange-listed American depositary receipts - Charitou, Andreas; Louca, Christodoulos (My University, 2009)
In this paper we examine the operating performance of non-US firms that enter major US stock exchanges using American Depositary Receipt (ADR) programs. Our dataset consists of 108 capital-raising and non-capital-raising firms from twenty four countries, cross-listed on major US stock exchanges during the period 1994-2004. We provide evidence that capital-raising cross-listed firms experience improvements in their operating performance after the listing, relative to a non-cross-listed matched sample of firms and relative to the pre-listing period, whereas non-capital-raising cross-listed firms out-perform a non-cross-listed matched sample of firms for both the pre-listing and the post-listing periods. These results suggest that the type of ADR program conveys information about changes in the post-listing operating performance. Moreover, both capital-raising and non-capital-raising cross-listed firms have positive abnormal returns due to the cross-listing and these abnormal returns are positively related with the post-listing abnormal changes in operating performance, suggesting that the market anticipates the post-listing abnormal changes in operating performance. Results are robust after adjusting for various firm and country risk characteristics.
Keywords: Cross-listing; Level II; Level III; Operating performance